Ewangelizacja Izraela w Liście do Efezjan - Adamczewski, Bartosz (Verbum Vitae, 2002)
According to the Letter to the Ephesians, evangelisation of Israel is not less important than evangelisation of the Gentiles. Israel, though it has been granted several privileges as the People of Covenants (Eph 2,12), is still in need of reconciliation and peace with God and with other nations (2,3.14-17). Only by accepting the gospel of Christ Israel – together with Gentile Christians – will achieve salvation (1,13) and will become new creation (2,15) living really near to God (2,13) and having access to the Father in the Spirit (2,18). All of the faithful Israelites (not only the sons of Levi) will then have the possibility of living always in direct nearness to God as holy priests of the spiritual temple of the Lord (2,19-21). Only through the gospel Israel will finally know God’s hidden „mystery” (3,3n.9) and the unsearchable richness of God’s grace (3,8) and wisdom (3,10), consisting in uniting Jewish and Gentile believers into one, reconciled community of the Body of Christ (3,6).